Governing the water user: experiences from Mexico. Issue 3 (4th May 2017) - Rap, Edwin; Wester, Philippus
ABSTRACT: This article traces a policy shift that makes the 'water user' the main subject of water governance. From a Foucauldian perspective on governmentality these new subjectivities accompany neo-liberal governmental technologies to devolve autonomy from state institutions to an active user base, whilst retaining some 'control at a distance'. The expectation is that individual subjects will incorporate control mechanisms and internalize norms and that this leads to new publicly auditable forms of self-regulation. The article questions the underlying assumption that policy necessarily accomplishes its strategic effects through governmentality. For this purpose, it draws on an ethnographic case study of how policy produced a new power/knowledge regime and how different societal actors and 'user' groups responded to that. The study specifically investigates the Mexican policy of irrigation management transfer during the 1990s, by which government transferred the public control over irrigation districts to locally organized water users' associations (WUAs). The article argues that governmental technologies make and govern the 'water user' by discursively and materially constituting an organizational arrangement for user management (WUA), more than by directly acting on individuals' self-regulated conduct. The analysis contributes to a broader reflection on the role of power/knowledge in natural resources management and decentralized resources governance.